Efficiency of Permanent Pastures Located at Different Altitudes, According to the Climatic Gradient Evolution - Neculai Dragomir; Dorin Rechiţean; Ioan Pet; Carmen Dragomir; Corina Cristea; Maria Sauer; Ioan Tapalaga; Darius Vacariu (Scientific Papers Animal Science and Biotechnologies, 2023)
This work presents the influence of climatic resources (rainfall and temperature) on the efficiency of permanent pastures located at different altitudes. The utilization degree of these climatic gradients was expressed successive to the determination of the following indices: the unitary efficiency of dry matter (Rup) and specific intake of rainfall water (Csa) and the unitary efficiency of dry matter (Ruc) and specific heat intake. The quantitative assessment of these productivity indices proves the influence exerted by altitude on permanent pastures’ efficiency.